2013
DOI: 10.1007/s00404-013-2721-3
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR C677T polymorphism was an ethnicity-dependent risk factor for cervical cancer development: evidence based on a meta-analysis

Abstract: This meta-analysis suggested that there was no association between MTHFR A1298C polymorphism and cervical cancer risk. However, MTHFR C677T was an ethnicity-dependent risk factor for cervical cancer occurrence. In addition, T allele of C677T was significantly associated with risk of low grade of CIN incidence. Because of modest limitations of our study, well-designed studies with large sample size were needed to confirm our findings in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Some meta-analysis found that MTHFR C677T polymorphism is associated with cervical carcinogenesis differently according to ethnic group, acting as a risk factor for Asian, and as a protective factor for Caucasian [13,14]. However, our study was performed with Brazilian women, a population composed by many mixed ethnicities.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Some meta-analysis found that MTHFR C677T polymorphism is associated with cervical carcinogenesis differently according to ethnic group, acting as a risk factor for Asian, and as a protective factor for Caucasian [13,14]. However, our study was performed with Brazilian women, a population composed by many mixed ethnicities.…”
Section: Discussionmentioning
confidence: 96%
“…Meta-analyses observed that C677T MTHFR polymorphism may be associated with cervical carcinogenesis in a different way according to ethnicity. This SNP was considered risk factor for cervical cancer among Asiatic women, but protection factor for Caucasian [13,14,35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of unveilings indicated that the MTHFR polymorphisms were associated with susceptibility of CC (Delgado‐Enciso et al, ; Kohaar et al, ; Wu, Yang, Lin, Li, & Wen, ). The current study provided the evidence that the SNP rs4846048 of MTHFR was associated with the increased CC risk.…”
Section: Discussionmentioning
confidence: 99%
“…As this cycle is the only pathway that gives methyl group in both biosynthesis of cellular compounds such as creatine, epinephrine, carnitine, phospholipids, proteins, and polyamines and in epigenetic changes (like methylation of DNA, RNA, and histones) [57]. Nevertheless, HHcy mediated metabolic malfunctioning because of the higher circulating Hcy levels promote oxidant stress-induced vascular inflammation and vessel dysfunction leading to atherosclerosis, myocardial infarction, stroke, multiple sclerosis, cognitive impairment, epilepsy, dementia, Parkinson's disease, and ocular disorders [58,59].…”
Section: Genetics Of Homocysteinaemiamentioning
confidence: 99%